Pediatric Resident Sign-out Education - Erin Shaughnessy (Association of American Medical Colleges, 2011)
Abstract In an era of increasing resident work-hour restrictions, handoffs of hospitalized patients have become more frequent. Multiple studies have shown that poor handoffs have significant negative consequences for patients. Daily handoffs by pediatric interns in the hospital setting, an activity known as "sign-out," represent perhaps the most vulnerable handoffs for hospitalized patients. Therefore, standardization, education, and training for intern sign-out are critical for patient safety. At the Medical College of Wisconsin, we have developed a standard format, SAFETIPS, for resident sign-out on the pediatric inpatient wards and have implemented training in the form of a live workshop and online module. After a needs assessment at our pediatric program and a review of the handoff literature, SAFETIPS was developed using input from the literature, current residents, and faculty. We have also developed evaluation materials in the form of an observed standardized clinical encounter, simulation station, and separate ward-based standardized clinical observation form so that trainees may receive feedback regarding their performance. Since the implementation of this curriculum, residents have embraced the new format and on the inpatient wards practice it almost exclusively. We are currently studying the effect of this training on actual resident sign-out skills. Workshop evaluations from 2009 and 2010 showed that 100% of participants agreed or strongly agreed that the workshop would improve their clinical practice. In addition, 100% felt the time for didactics, small-group discussion, and pairs practice was just right.